ANALYSIS OF DISASTER RISK REDUCTION (DRR) LEARNING MODULES IN SCHOOL CURRICULUM IN INDONESIA - Signorina Kasvia; Mirza Desfandi (RADJA PUBLIKA, 2024)
Schools need a disaster module as a special guide that is used to build student awareness in dealing with disasters. To meet the needs of students as users, this module must be able to deliver accurate and trustworthy information. This paper uses a descriptive qualitative approach with content analysis, which explains in more depth what school DRR support modules have been developed. There are four steps to this research method: i) problem conceptualization, ii) data collecting (investigation), iii) data coding, and iv) data analysis and interpretation. This study uses search engines from databases such as Google, and data from the National Secretariat, KIE Media, and Schools. This paper will discuss further i) What DRR support modules have been developed in schools? ii) how is the module compatible with disaster learning? and iii) How suitable is the module for disaster learning in schools? To support a wider spectrum of literature emerging from the search, the database was searched using the following key terms: “Modules”, “Learning”, “Disasters”, “Schools”, “DRR”, “Training”, “Teachers” adding “AND”